Simulation of Loads on the Carrying Structure of an Articulated Flat Car in Combined Transportation - Lovska, Alyona; ., . (International Journal of Engineering and Technology, 2018)
The article presents the findings of the research into loading on the carrying structure of an articulated flat car under combined transportation. The refined data of dynamic loads on the carrying structure of a flat car under train ferry transportation, as well as the main loading modes in rail track operation were determined by mathematical modeling. The adequacy of the models developed was checked with an F-test. The results of the calculation conducted made it possible to conclude that the hypothesis on adequacy of the models is not rejected. The peculiarities of the structural strength modeling for a flat car within operational loading diagrams are given. The graphics works were conducted in Solid Works. The capacity analysis was conducted by the finite element method in CosmosWorks. The 09G2S steel was used as a construction material. It is determined that the maximum equivalent loads in the flat car support structure do not exceed the admissible loads. Results of the research can be used in designing coupled flat cars to provide their capacity at mixed transportation. Â